Triatomine (Hemiptera: Reduviidae) populations and Trypanosoma cruzi genotyping in peridomestic and sylvatic environments in the semiarid region of Sergipe, Northeastern, Brazil - Fontes, Felipe Mendes (2024)
We assessed the diversity of triatomines, the rates of natural infection, and the discrete typing units (DTUs) of Trypanosoma cruzi isolated from them in two municipalities in the state of Sergipe, Brazil. Active searches for triatomines were conducted in the peridomicily and wild enviroments of 10 villages within the two municipalities. Triatomines were taxonomically identified and their feces were extracted using the abdominal compression method. Parasite detection was performed using optical microscopy. For Trypanosoma cruzi genotyping via PCR-FFLB, 151 samples of the subspecies Triatoma brasiliensis macromelasoma and Triatoma brasiliensis were isolated from both municipalities. In total, 505 triatomines were collected, with Triatoma brasiliensis macromelasoma being the most frequent species (58.81 %). Triatoma b. brasiliensis was the only species in both peridomestic and wild environments. Regarding the other species, T. pseudomaculata was found only in the peridomestic environment; and T. b. macromelasoma and Psammolestes tertius were found in the wild environment. Three Discrete Typing Units were identified: TcI (87.51 %) detected in T. b. brasiliensis and T. b. macromelasoma, TcI+TcIII (10.41 %) in T. b. macromelasoma, and TcI+Trypanosoma rangeli (2.08 %) in T. b. macromelasoma. It is concluded that T. b. macromelasoma is the species collected most frequently in the studied region and the one that presents the highest rates of natural infection, highlighting its epidemiological importance for the vectorial transmission of Chagas disease in Sergipe.